Benign versus life-threatening causes of pneumatosis intestinalis: differentiating CT features - Ko,Sujin (2018)
SUMMARY OBJECTIVE: To assess the diagnostic performance of CT findings in differentiating causes of pneumatosis intestinalis (PI), including benign and life-threatening causes. METHODS: All CT reports containing the word “pneumatosis” were queried from June 1st, 2006 to May 31st, 2015. A total of 42 patients with PI were enrolled (mean age, 63.4 years; 23 males and 19 females) and divided into two groups on based on electronic medical records: a benign group (n=24) and a life-threatening group (n=18). Two radiologists reviewed CT images and evaluated CT findings including bowel distension, the pattern of bowel wall enhancement, bowel wall defect, portal venous gas (PVG), mesenteric venous gas (MVG), extraluminal free air, and ascites. RESULTS: CT findings including bowel distension, decreased bowel wall enhancement, PVG, and ascites were more commonly identified in the life-threatening group (all p<0.05). All cases with PVG were included in the life-threatening group (8/18 patients, 44.4%). Bowel wall defect, extraluminal free air, and mesenteric venous gas showed no statistical significance between both groups. CONCLUSION: PI and concurrent PVG, bowel distension, decreased bowel wall enhancement, or ascites were significantly associated with life-threatening causes and unfavorable prognosis. Thus, evaluating ancillary CT features when we encountered PI would help us characterize the causes of PI and determine the appropriate treatment option.